Oxymetholone Therapy in Patients with Familial Antithrombin III Deficiency - Shibuya, Akira; Ninomiya, Haruhiko; Nakazawa, Masaki; Nagasawa, Toshiro; Yoda, Yasuhiro; Abe, Tsukasa (Thrombosis and Haemostasis, 1988)
Three patients with familial antithrombin III (ATIII) deficiency, who also have histories of thromboembolism, were treated with oxymetholone in combination with warfarin. Thrombolysis was observed in one patient with acute thrombosis of inferior vena cava during the oxymetholone and warfarin therapy. No further thromboembolic episodes occurred in these patients after initiation of warfarin with or without oxymetholone. The levels of plasma ATIII, α1-antitrypsin, plasminogen and Cl-inactivator were significantly increased in all patients after the introduction of oxymetholone therapy. This suggests that oxymetholone augments anticoagulant and fibrinolytic activity. Hence we consider that oxymetholone in combination with warfarin may be possible thrombolytic therapy in patients with familial ATIII deficiency.
Keywords: Familial antithrombin III deficiency; Thromboembolism; Thrombolysis; Oxymetholone; warfarin